การเขียนบทความทางวิชาการ - เนืองเฉลิม ประสาท (Journal for Developing the Social and Community, 2016)
An academic article is a product of analytical and synthetic writing reflecting author’s knowledge and capability in academic work and communication. This article aims to present concepts and experiences writing about academic article which it can be implied for those academician uses.